Analysis of Research Management by the National Research and Innovation Agency: Politicization of Research or Opportunities for Realizing Evidence-Based Policy? - Syafruddin Syafruddin; Novi Indah Earlyanti (UIN Sunan Gunung Djati, 2023)
Numerous experts recommend the adoption of evidence-based policy concepts to ensure the high quality of policy decisions and practices. Research plays a crucial role in this context, serving as an instrumental process to inform policy decisions at various levels. In contrast to some countries that have established independent, autonomous, and decentralized research institutions, Indonesia's recent shift towards centralization through the creation of the National Research and Innovation Agency has raised concerns about potential politicization of research. This article seeks to analyze the risk of research politicization and explore prospects for future research management to support the implementation of evidence-based policies. Employing a qualitative approach, this study relies on a thorough literature review, drawing from reputable journals, books, and other credible references. The results indicate that the existence of the National Research and Innovation Agency offers a dual perspective: while it enables government control over research implementation aligned with political agendas, it also opens avenues for utilizing research findings in diverse policy decisions and practices. Emphasizing objectivity is essential as research must remain impartial. Therefore, future research management should prioritize objectivity, and the format of the National Research and Innovation Agency presents an opportunity to promote evidence-based policies and policy practices grounded in unbiased research outcomes.